Synthesis of resveratrol sulfates: turning a nightmare into a dream. Issue 20 (20th May 2015) - Mattarei, Andrea; Biasutto, Lucia; Romio, Matteo; Zoratti, Mario; Paradisi, Cristina
Abstract: The growing interest in the bioactivity of natural polyphenols and of their metabolites requires pure metabolites to be used in bioassays and as standards in analytical protocols. We report here the synthesis of all five resveratrol sulfates achieved using a known approach of selective protection via silyl ether and sulfation but new reaction conditions and isolation procedures, which result in simplified protocols and greatly improved yields. A rationale for the problems so far encountered in handling and isolating resveratrol sulfates is provided as well as a solution based on avoidance of low pressure conditions during purification/isolation. These conclusions are probably of more general scope and might be usefully taken into consideration for obtaining other phenolic sulfates in high yield. Graphical abstract: